2013
DOI: 10.2209/tdcpublication.54.141
|View full text |Cite
|
Sign up to set email alerts
|

Does Mandatory Postgraduate Clinical Training Worsen Geographic Distribution of Dentists in Japan?

Abstract: Postgraduate clinical training for dentists has been mandatory in Japan since 2006. Hirata et al. reported that the geographic distribution of postgraduate dental trainees by prefecture in 2006 was worse than that of practicing dentists. This suggests that the postgraduate clinical training system could intensify the problem of distribution of dentists. In this study, therefore, we reviewed the geographic distribution of postgraduate dental trainees and practicing dentists between 2006 and 2010 in detail by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 10 publications
0
10
1
Order By: Relevance
“…At governorate level, the number of dental graduates had a weak association with dentist availability. This disagrees with previous reports that the presence of a dental school had a positive effect on dentist availability at county level in the United States of America (1) and in Japanese prefectures (25). However, it agrees with a study assessing the relationship at the American state level (26); a larger unit that may be more similar to the areas in our study.…”
Section: Discussioncontrasting
confidence: 96%
“…At governorate level, the number of dental graduates had a weak association with dentist availability. This disagrees with previous reports that the presence of a dental school had a positive effect on dentist availability at county level in the United States of America (1) and in Japanese prefectures (25). However, it agrees with a study assessing the relationship at the American state level (26); a larger unit that may be more similar to the areas in our study.…”
Section: Discussioncontrasting
confidence: 96%
“…Although the geographical distribution of PGYD in Japan has not gone even more dispersed within the 5-year time of implementation, the continuous issues about the geographical distribution trend of dentist in practice and its effect deserve further concern 12 . Just as the situation in Japan, the geographical distribution of the training institutions in Taiwan has great regional bias.…”
Section: Discussionmentioning
confidence: 99%
“…This is based on the global standards proposed by the World Federation for Medical Education (1,2). Cross-sectional studies for each period have been reported regarding education at the pre-graduate clinical practical training and post-graduate clinical training levels (3)(4)(5)(6)(7)(8)(9). However, no studies on a clinical competency examination as an overall evaluation at the end of pregraduate clinical practical training and at the end of OSCAT as a pilot study with the objective of establishing a clinical competency evaluation for professionalism in dental education.…”
Section: Introductionmentioning
confidence: 99%